The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0104-77602011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Estabelecimento in vitro de Peltophorum dubium ((Spreng.) Taub.) em função das concentrações do meio MS

Abstract: RESUMO:Neste trabalho, objetivou-se verificar a influência de diferentes concentrações do meio MS no estabelecimento in vitro de segmentos apicais caulinares (80-100 mm) de canafístula isolados, a partir de plântulas germinadas em condições assépticas. As concentrações de sais de 50, 75, 100, 125 e 150% do meio de cultivo MS, foram suplementadas com 30 g L -1 de sacarose, 100 mg L -1 de mio-inositol, 7 g L -1 de ágar e o pH, ajustado para 5,7. O delineamento experimental foi o inteiramente casualizado, com 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The first studies on the micropropagation of P. dubium focused on aspects of in vitro establishment and multiplication (BASSAN et al, 2006;CURTI et al, 2010a;CURTI et al, 2010b;FLÔRES et al, 2011). They indicated that the species is suitable for asexual propagation but also identified a need for additional studies on in vitro multiplication and rhizogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The first studies on the micropropagation of P. dubium focused on aspects of in vitro establishment and multiplication (BASSAN et al, 2006;CURTI et al, 2010a;CURTI et al, 2010b;FLÔRES et al, 2011). They indicated that the species is suitable for asexual propagation but also identified a need for additional studies on in vitro multiplication and rhizogenesis.…”
Section: Introductionmentioning
confidence: 99%